Flash glucose monitoring in young people with type 1 diabetes—a qualitative study of young people, parents and health professionals: ‘It makes life much easier’ - Lucy Beasant; Jenny Ingram; Rebecca Kandiyali; Julian P H Shield; Elizabeth Thomas; Nicol West; Freyja Cullen; David Mcgregor (BMJ Open)
Objectives Flash glucose monitoring for patients with T1 diabetes avoids frequent painful finger-prick testing, thus potentially improving frequency of glucose self-monitoring. Our study aimed to explore experiences of young people using Freestyle Libre sensors and their parents, and to identify benefits and challenges to National Health Service (NHS) staff of its adoption in their care provision.Participants Young people with T1 diabetes, their parents and healthcare professionals were interviewed between February and December 2021. Participants were recruited via social media and through NHS diabetes clinic staff.Design Semistructured interviews were conducted online and analysed using thematic methods. Staff themes were mapped onto normalisation process theory (NPT) constructs.Results Thirty-four participants were interviewed: 10 young people, 14 parents and 10 healthcare professionals. Young people reported that life was much easier since changing to flash glucose monitoring, increasing confidence and independence to manage their condition. Parents’ quality of life improved and they appreciated access to real-time data. Using the NPT concepts to understand how technology was integrated into routine care proved useful; health professionals were very enthusiastic about flash glucose monitoring and coped with the extra data load to facilitate more tailored patient support within and between clinic visits.Conclusion This technology empowers young people and their parents to understand their diabetes adherence more completely; to feel more confident about adjusting their own care between clinic appointments; and provides an improved interactive experience in clinic. Healthcare teams appear committed to delivering improving technologies, acknowledging the challenge for them to assimilate new information required to provide expert advice.